1982
DOI: 10.1128/jvi.43.2.555-565.1982
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for two classes of chromatin-associated Epstein-Barr virus-determined nuclear antigen

Abstract: A new class of Epstein-Barr virus nuclear antigen (EBNA) was identified by the complement fixation assay. This new species of EBNA is more tightly bound to chromatin and was termed class II EBNA, as opposed to the more weakly associated species, class I EBNA. Preparations of this new antigen(s) specifically reduced absorption with the titer of anti-EBNA antibodies as determined by the anticomplement immunofluorescence assay. Therefore, the complement fixation antigens (class II EBNA) appear to be related to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1984
1984
1986
1986

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The 72K EBNA protein is heterogeneous in isoelectric point and chromatin binding (16,17;Luka et al., submitted for publication) and is encoded by an EBV DNA fragment which contains the IR3 repetitive element (2, 3, 5-7). The correct reading frame for translation of this EBV gene is known from the nucleotide sequence of a fusion gene between EBV IR3 and lac Z since the fusion gene codes for a protein with epitopes of EBNA (8).…”
mentioning
confidence: 99%
“…The 72K EBNA protein is heterogeneous in isoelectric point and chromatin binding (16,17;Luka et al., submitted for publication) and is encoded by an EBV DNA fragment which contains the IR3 repetitive element (2, 3, 5-7). The correct reading frame for translation of this EBV gene is known from the nucleotide sequence of a fusion gene between EBV IR3 and lac Z since the fusion gene codes for a protein with epitopes of EBNA (8).…”
mentioning
confidence: 99%
“…More recent evidence has demonstrated the existence of multiple EBV-specific antigens in EBV-transformed cells. The most prominent antigen (EBNA 1) is a polypeptide partially encoded by the BamHI K fragment, and the second (EBNA 2) is a polypeptide encoded by the BamHI WYH region (3,4,6,8,(19)(20)(21).…”
mentioning
confidence: 99%
“…Strnad et al (24), using fluoroimmunoelectrophoresis to detect EBNA, noted the presence of an additional 81,000molecular-weight (81K) antigen in B95-8 and Raji cells. Spelsberg et al (23) presented evidence for the existence of two distinct components of the EBV-induced nuclear antigen in NC37 cells. Hennessy and Kieff (7), employing protein immunoblots, observed that some EBV-immune human antisera recognized a second intracellular antigen that was specific for latently infected cells.…”
mentioning
confidence: 99%